1995
DOI: 10.1029/95jc00473
|View full text |Cite
|
Sign up to set email alerts
|

Observation of internal tides in the East China Sea with an underwater sliding vehicle

Abstract: Detailed structures of internal tides in the East China Sea were observed during autumn from 1986 to 1989, using an underwater sliding vehicle that can measure temperature, conductivity, and depth continuously, sliding up and down along a faired cable. A variety of structures were observed and are classified with internal Froude numbers of the lowest two modes, which depend on the barotropic tidal current velocities and the phase speeds of internal waves (i.e., stratification). In the central East China Sea, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…These narrow areas are located on either side of the Kuroshio jet, where internal waves were frequently observed (Kuroda and Mitsudera, 1995;Liu et al, 1998;Han et al, 2001;Park et al, 2006). Using a twodimensional analytical model, Baines (1982) predicted that the slope of the continental shelf in the ECS and its adjacent area is the second largest generator of the M 2 internal tides among the major continental shelf slopes in the world's oceans.…”
Section: Variability Of Turbulence Intensity and Turbulent Nitrate Fluxmentioning
confidence: 95%
See 1 more Smart Citation
“…These narrow areas are located on either side of the Kuroshio jet, where internal waves were frequently observed (Kuroda and Mitsudera, 1995;Liu et al, 1998;Han et al, 2001;Park et al, 2006). Using a twodimensional analytical model, Baines (1982) predicted that the slope of the continental shelf in the ECS and its adjacent area is the second largest generator of the M 2 internal tides among the major continental shelf slopes in the world's oceans.…”
Section: Variability Of Turbulence Intensity and Turbulent Nitrate Fluxmentioning
confidence: 95%
“…Indeed, a series of studies revealed that internal waves intermittently generated around the shelf break of the ECS and the ridges along the Ryukyu Archipelago could induce enhanced vertical mixing. Consequently, it has been hypothesized that this process may support new production (Kuroda and Mitsudera, 1995;Matsuno et al, 1997Matsuno et al, , 2005Han et al, 2001;Lee et al, 2006;Park et al, 2006). Repeated hydrographic surveys across the shelf break showed that the vertical structure formed by an intensified thermocline and bottom or intermediate mixed layer could change daily (Han et al, 2001).…”
Section: Variability Of Turbulence Intensity and Turbulent Nitrate Fluxmentioning
confidence: 96%
“…The NIOs can cause energy and mass exchange between the East China Sea and the Kuroshio region (Kuroda and Mitsudera, 1995), and therefore, they play important roles in ocean dynamics, biological productivity and sedimentary processes along the margin of the continental shelf. However, the more detailed investigation of their structures and processes would require simultaneous observations of temporal evolution of temperature, salinity and velocity fields and so awaits further study.…”
Section: Semidiurnal Currents and Near-inertial Oscillations Altered mentioning
confidence: 99%
“…An extensive literature describing the variety of fluid processes associated with stratified flow over bathymetry exists. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To the authors' knowledge, the only theoretical or numerical study of acoustic propagation through flow controlled sound-speed fields was done by Sherwin. 16 He presented numerical simulations that related variations in the sound-speed field to tidal flow across a continental shelf break and slope.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Shallow water currents are largely driven by the tide. Consequently, acoustic signals propagating over fixed paths in the continental shelf and slope environment are expected to be temporally variable and exhibit some degree of repeatability in their properties over a tidal cycle.…”
Section: Introductionmentioning
confidence: 99%